The IONWI algorithm: learning when and when not to interrupt - Schiaffino, Silvia (2006)
One of the key issues for an interface agent to succeed at assisting a user is learning when and when not to interrupt him to provide him assistance. Unwanted or irrelevant interruptions hinder the user’s work and make him dislike the agent because it is being intrusive and impolite. The IONWI algorithm enables interface agents to learn a user’s preferences and priorities regarding interruptions. The resulting user profile is then used by the agent to personalize the modality of the assistance, that is, assisting the user with an interruption or without an interruption depending on the user’s context. Experiments were conducted in the calendar management domain, obtaining promising results.